Corporate governance and financial reform in China's transition economy - Leng, Jing, 1974- (Hong Kong University Press, 2009)
This work explores the basic concepts of corporate governance and global movements in corporate governance reforms, the corporate governance reform of China's banking system, the Chinese experience in international corporate governance debates, and much more.